Facilitating the social behaviour of bull elephants in zoos. Issue 1 (10th October 2019) - Hartley, M.; Wood, A.; Yon, L.
Abstract : Bull elephants socialize with conspecifics of all ages and both sexes; and young bulls develop social bonds with other elephants that will be sustained throughout their lives. However, it is complex and challenging in zoos to build facilities and manage groups of elephants in ways that allow fission–fusion herd dynamics and give the elephants choice over their environment. To advance the development of best‐practice management for zoo elephants it is necessary to improve our understanding of the social and behavioural needs of bull elephants, and implement innovative solutions to their care. This paper considers the social behaviour of bull elephants, contributes novel preliminary data about how these issues are addressed and proposes some new approaches to the management of bull elephants in zoos. (Photo: Lisa Yon, University of Nottingham) Abstract : In the wild, bull elephants socialize with conspecifics of all ages and both sexes, and young bulls develop social bonds with other elephants which will be sustained throughout their lives. Significant progress has been made towards providing an environment that facilitates social behaviour and multi‐generational family structure for female elephants in zoos. However, it is more complex and challenging to build facilities and manage groups of elephants in ways that allow fission–fusion herd dynamics and give the elephants choice over their environment. For bulls, this is further complicated by their potential strength and aggressive behaviour. To advance the development of best‐practice management for zoo elephants and achieve high standards of welfare, it is necessary to improve our understanding of the social and behavioural needs of bull elephants, and implement radical and innovative solutions to their care. In this paper we (1) consider how the social behaviour of bull elephants is addressed in zoos, comparing their social management with their behaviour in the wild, (2) contribute novel preliminary data about how these issues are addressed, and (3) propose some new approaches to the management of bull elephants in zoos for the future.